남부지역 논의 밀 이모작에서 하계 곡실작물 도입의 적합성 - 서종호; Jong-ho Seo; 황정동; Chung-dong Hwang; 오성환; Seong-hwan Oh (Korean journal of crop science, 2021)
The growth period and productivity of cropping system of winter wheat-rice, winter wheat-bean and winter wheat-grain corn for 4 years from 2015 to 2018 were compared at the experimental field of National Institute of Crop Science in Miryang city. The harvest period of winter wheat was in mid-June, and summer crops were sown (transplanted) in late June. In transplanting of rice in late June, there was no difficulty in securing the heading of panicle and the yield of rice, but there was a lot of trouble in sowing wheat in proper time because the harvest time of rice was delayed to early November due to late maturity of rice, particularly in the mid-late maturing cultivar. There was no problem in soybean planting after winter wheat because the proper period of soybean planting is late-June. In addition, there was no problem in winter wheat sowng after soybean because the maturity period of soybean was mid-October. Selection of grain maize in double cropping with winter wheat in terms of growing periods, was desirable because grain maize had the fastest maturity among summer crops. In double cropping of winter wheat-summer crops, wheats combined with soybean and grain maize showed stable yields during three years, but there was a risk of yield declines in the wheat combined with rice in heavy rainfall year. It was possible to secure high yields in three summer crops as yields of rice, soybean, and corn were 600, 350, and 800 kg/10a, respectively. Summer crops with medium maturity was recommended because of no significant difference in yield between medium maturity and medium-late maturity cultivar. Soil physical properties were improved in soils cultivated with soybean and grain maize. Therefore, It was thought that double cropping systems of winter wheat with soybean and grain maize were superior to that of winter wheat with rice in terms of connecting period between winter wheat - summer crops and improvement of soil physical properties, and total income, particularly in soybean.